Statistical Analysis of The Use of Electronic Learning Guides in Higher Education Institutions - Israilov Sharobiddin Makhammadyusufovich (Periodica Journal, 2023)
This the article presents the statistics of the increase in educational efficiency when teaching using electronic textbooks in higher education institutions
Keywords: multimedia; teaching; resources; training